Numerical Investigation of the Ultimate Load-Carrying Capacity of Square Concrete-Filled Steel Tube Columns Considering Initial Stresses Generated during Construction - Huizhong Xue; Kaozhong Zhao; Fengmin Xia; Guangyi Wang; Ao Shen (Buildings, 2023)
During construction, newly cast concrete exerts lateral pressure on the steel plates of concrete-filled steel tube (CFST) columns, resulting in non-negligible initial circumferential stresses. Finite element analysis, in which lateral pressure is applied using a user-defined load subroutine, was conducted to comprehensively investigate the effects of initial stresses, including circumferential stresses, on the structural behaviors of a square CFST column under the action of compressive load. This study also provides guidance for the numerical simulation of CFST columns under complicated construction scenarios. The analysis revealed that the steel tube plates were more sensitive to lateral pressure, which should be limited during construction, compared with gravity loads. Under the action of compressive load, the presence of initial stresses altered the failure modes of the square CFST columns and reduced their ultimate load-carrying capacities (ULCCs). For columns with slenderness ratios of 18 and 37, the ULCCs were essentially inversely proportional to the initial stress ratio β, ranging from 0.1 to 0.5. However, for columns with a larger slenderness ratio of 55, the initial stress level did not influence their ULCCs. Finally, a simple method for calculating the ULCCs of square CFST columns considering initial stresses is proposed for design purposes.